2018
DOI: 10.1017/s1751731117003329
|View full text |Cite
|
Sign up to set email alerts
|

In vitro supplementation with the porcine plasma product, betaGRO®, stimulates activity of porcine fetal myoblasts and neonatal satellite cells in a divergent manner

Abstract: Two separate experiments were conducted to evaluate the effect of betaGRO ® supplementation on in vitro porcine fetal myoblasts (PFM) and porcine satellite cells (PSC) proliferation, fusion and myotube thickness. The PFM and PSC were isolated from the m. longissimus dorsi of day 60 of gestation fetuses and piglets within 24 h of birth, respectively. Proliferation assays were conducted as 4 × 3 factorial arrangements with time of culture (24, 48, 72, 96 h) and media treatment (standard porcine media supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Therefore, the response to BG and CT supplementation is likely not nutritive but due to metabolic improvements. Recent research has demonstrated that BG promoted immune cell function and skeletal muscle growth in vitro [24,25]. Inclusion of BG in culture medium at 10 mg/mL resulted in significantly larger myotube size and was mediated by positive changes in mechanistic target of rapamycin (mTOR) signaling proteins [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the response to BG and CT supplementation is likely not nutritive but due to metabolic improvements. Recent research has demonstrated that BG promoted immune cell function and skeletal muscle growth in vitro [24,25]. Inclusion of BG in culture medium at 10 mg/mL resulted in significantly larger myotube size and was mediated by positive changes in mechanistic target of rapamycin (mTOR) signaling proteins [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that BG promoted immune cell function and skeletal muscle growth in vitro [24,25]. Inclusion of BG in culture medium at 10 mg/mL resulted in significantly larger myotube size and was mediated by positive changes in mechanistic target of rapamycin (mTOR) signaling proteins [24]. Immune research previously conducted observed that BG supplementation increased respiratory metabolism of actively growing β-lymphocyte cells by more than two-fold, which was mediated by mTOR pathway signaling since the addition of rapamycin abolished all positive treatment effects [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation